One flag, one land - Brown, Richard Carl; Greer, Lawrence N.; Bass, Herbert J.; Silver Burdett Ginn (Firm) (Silver, Burdett & Ginn, 1988)
A textbook chronicling the birth and growth of the United States through the 1980's.
Includes bibliographical references and index.
[v.1. Student text] -- [v.2] Annotated teacher ed. -- [v.3] Workbook -- [v.4] Workbook (teacher ed.) / Lawrence N. Greer, Jr. -- [v.5] Teacher planning guide / Larry Greer ... [et al.] -- [v.6] Test masters -- [v.7] Practice masters -- [v.8] Outline map masters.
A textbook chronicling the birth and growth of the United States through the 1980's.
Keywords: Social sciences / Study and teaching (Secondary); United States / History / Study and teaching (Secondary)